Advantages of intensity modulated proton therapy during hippocampal avoidance whole brain radiation therapy. (October 2018) - Stoker, Joshua; Vora, Sujay; Patel, Ameet; Grosshans, David; Brown, Paul D.; Vern-Gross, Tamara; Bues, Martin; Daniels, Thomas; Allred, Bryce; Uejo, Arielle; Kosiorek, Heidi; Bruso, Marlene; et al.
Highlights: Whole-brain intensity modulated proton therapy capably spares hippocampal volumes. Hippocampal avoidance whole-brain radiotherapy may benefit pediatric populations. Intensity modulated proton therapy provides superior target-dose homogeneity relative to modulated x-rays. Abstract: Background and purpose: Intensity modulated proton therapy (IMPT) allows for modulation parameterized for individual beamlets by position, intensity, and depth. This modulation capability is ideally suited for sparing organs at risk intermediate of the radiation target, such as hippocampal volumes within the whole brain. This work compared IMPT relative to volumetric modulated arc therapy (VMAT) during hippocampal avoidance whole brain radiation therapy (HA WBRT). Materials and methods: Ten adult and ten pediatric patients previously treated for central nervous system malignancies were identified. IMPT and VMAT treatment plans employing HA WBRT were generated for each patient, delivering 30 GyE (Gray Equivalent) in 10 fractions for adults and 36 GyE in 20 fractions for pediatrics. Dose indices, including dose volume histogram metrics and homogeneity index HI = [D5% − D95%]/[Dmean ] × 100, were used to assess plan quality and describe target coverage and normal-tissue sparing. Results: IMPT offered significant benefits relative to VMAT for hippocampal sparing. Hippocampal mean dose was reduced from 13.7 ± 0.8 Gy with VMAT to 5.4 ± 0.3 GyE using IMPT for pediatrics, and was reduced from 11.7 ± 0.9 Gy with VMAT to 4.4 ± 0.2 GyE using IMPT for adults. IMPT similarly lowered left hippocampal mean dose. Dose to 95% of the clinical target volume was statistically equivalent for both groups; however IMPT reduced the homogeneity index by roughly half. Conclusion: This manuscript demonstrates that HA IMPT can match or exceed dosimetric benefits offered with modulated X-rays. Inclusion of IMPT in future prospective studies is warranted.